Formation of water chains on CaO(001): What drives the 1D growth? - Zhao, Xunhua; Shao, Xiang; Fujimori, Yuichi; Bhattacharya, Saswata; Ghiringhelli, Luca M.; Freund, Hans Joachim; Sterrer, Martin; Nilius, Niklas; Levchenko, Sergey V. (Journal of Physical Chemistry Letters, 2015)
Formation of partly dissociated water chains is observed on CaO(001) films upon water exposure at 300 K. While morphology and orientation of the 1D assemblies are revealed from scanning tunneling microscopy, their atomic structure is identified with infrared absorption spectroscopy combined with density functional theory calculations. The latter exploit an ab initio genetic algorithm linked to atomistic thermodynamics to determine low-energy H2O configurations on the oxide surface. The development of 1D structures on the C4v symmetric CaO(001) is triggered by symmetry-broken water tetramers and a favorable balance between adsorbate-adsorbate versus adsorbate-surface interactions at the constraint of the CaO lattice parameter.
CRIS-Team Scopus Importer:2023-09-25
Keywords: 1D molecular assemblies; DFT global optimization; genetic algorithm; IR spectroscopy; oxide surfaces; scanning tunneling microscopy; water adsorption